2014
DOI: 10.1088/0004-6256/148/2/37
|View full text |Cite
|
Sign up to set email alerts
|

The ECLIPSING SYSTEM V404 LYR: LIGHT-TRAVEL TIMES AND Γ DORADUS PULSATIONS

Abstract: We present the physical properties of V404 Lyr exhibiting eclipse timing variations and multiperiodic pulsations from all historical data including the Kepler and Super-WASP observations. Detailed analyses of 2,922 minimum epochs showed that the orbital period has varied through a combination with an upward-opening parabola and two sinusoidal variations, with periods of P 3 =649 d and P 4 =2,154 d and semi-amplitudes of K 3 =193 s and K 4 =49 s, respectively. The secular period increase with a rate of +1.41 ×1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 54 publications
2
44
2
Order By: Relevance
“…They now provide third body LTTE solutions for seven EBs. Additional studies of a possible third body affecting the ETVs of individual EBs in the Kepler-field have also been reported in Steffen et al (2011, for KOI-928(=KIC 09140402)) Borkovits et al (2013, for HD 181068(=KIC 05952403)), Lee et al (2013, for KIC 02856960), Lee et al (2014, for V404 Lyr(=KIC 03228863)), Lee et al (2015, for KIC 05621294). Most recently, Baran et al (2015) reported the detection of a planet-mass companion in the sdB+dM EB 2M1938+4603(=KIC 09472174).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…They now provide third body LTTE solutions for seven EBs. Additional studies of a possible third body affecting the ETVs of individual EBs in the Kepler-field have also been reported in Steffen et al (2011, for KOI-928(=KIC 09140402)) Borkovits et al (2013, for HD 181068(=KIC 05952403)), Lee et al (2013, for KIC 02856960), Lee et al (2014, for V404 Lyr(=KIC 03228863)), Lee et al (2015, for KIC 05621294). Most recently, Baran et al (2015) reported the detection of a planet-mass companion in the sdB+dM EB 2M1938+4603(=KIC 09472174).…”
Section: Introductionmentioning
confidence: 67%
“…Unfortunately, the times of minima obtained from these data bases often offer only lesser benefits because of the restricted extension of the data span and, in several cases, the sampling rate of the observations of each EB was so infrequent that the data do not yield times of individual eclipses with useful accuracy. For these reasons we did not determine and utilize the times of minima from the observations of the above listed surveys for all systems, we make use of the data only for those EBs for which the eclipse times were determined by Lee et al (2014) and Zasche et al (2015).…”
Section: Supplemental Ground-based Eclipse Timingmentioning
confidence: 99%
“…The known γ Dor binaries whose period spacings were not previously measured are: KIC 3228863 (Lee et al 2019(Lee et al , 2014; KIC 4150611 (Hełminiak et al 2017); KIC 6048106 (Lee 2016;Samadi Ghadim, Lampens & Jassur 2018); KIC 6206751 (Lee & Park 2018); KIC 8569819 (Kurtz et al 2015); KIC 9236858 (Kjurkchieva & Atanasova 2016); and KIC 9851944 (Guo et al 2016). These works focused mainly on the dynamics of the binary systems, hence they did not measure the period spacings of g modes.…”
Section: Sample Selectionmentioning
confidence: 99%
“…The PERIOD04 program (Lenz & Breger 2005) was carried out in the frequency range from 0 to the Nyquist limit of f Ny =24.47 days −1 . After the successive prewhitening of each frequency peak (see Lee et al 2014), we detected the frequencies based on the empirical threshold of the signal-to-noise amplitude ratio (S/N) larger than 4.0 (Breger et al 1993). Third, we removed the pulsation signatures from the observed K2 data.…”
Section: Light-curve Residuals and Pulsational Characteristicsmentioning
confidence: 99%